Factors Associated With Job Satisfaction of Frontline Medical Staff Fighting Against COVID-19: A Cross-Sectional Study in China - Yu, Xiaoyan; Zhao, Yuxin; Li, Yuxi; Hu, Chao; Xu, Huilan; Zhao, Xianmei; Huang, Jin (Frontiers in Public Health, 2020)
Purpose: The current research on frontline medical staff in China fighting against COVID-19 has not yet addressed job satisfaction. The purpose of this study is to investigate the job satisfaction of those who were sent to support Hubei province, China, or worked in local designated hospitals, and then analyze the associated influencing factors. Materials and Methods: A total of 455 medical staff who worked at the frontline of the prevention and control of COVID-19 in Hubei province was selected using simple random sampling. They were asked to fill out a self-developed general information questionnaire as well as the Minnesota Satisfaction Questionnaire (MSQ), from 10 January to 10 March 2020. Results: The average job satisfaction score of the participants was 82.58 ± 11.11. The influencing factors include education (P = 0.002), years of work experience (P = 0.006), anti-epidemic work duration (P = 0.048), daily sleep duration (P < 0.001), and the form of participation (P < 0.001). Conclusions: This study, for the first time, measures the job satisfaction of frontline medical staff in fighting against COVID-19 in China. The job satisfaction of frontline medical staff was at a “relatively decent” level, higher than the previous similar measures among medical staff. Related management departments should further improve the job satisfaction of frontline medical staff by meeting their reasonable demands, strengthening the emergency response and practical operation training of junior staff, and ensuring their ample time for sleep and rest. This study is of great reference value for improving the job satisfaction level of frontline medical staff during public health emergencies, developing medical staff security policies, and promoting the establishment of emergency response teams.